Radioactive Pollution and Biological Effects of Radioactivity (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue “Radioactive Pollution and Biological Effects of Radioactivity“of the Journal Life involved the participation of academic scientists, researchers, and scholars from all over the World that contributed with articles, reviews, and case reports, based on high-quality research works.The common topic of the published works concerns the radioactive pollution, which occurs when radioactive elements enter the atmosphere and reach the Earth’s surface, within solids, liquids, or gases, including the human body. This happens after natural and/or man-made activities, such as nuclear tests, industrial waste (e.g., radiodiagnostics), and excesses of naturally occurring radioactive sources. This kind of pollution entails risks of radiological contamination of the environment, with harmful effects on human health caused by the ionizing radiation. This theme has become even more current due to the increasing use of ionizing radiation for domestic, industrial, and medical purposes during the last century. Radiological monitoring is a primary objective of radiation protection in order to estimate and understand the impact of radionuclides on the environment and to assess the health risk for the population.The aim of the Special Issue has been to provide an interdisciplinary platform for researchers to exchange and share their experiences and latest achievements on all aspects of radioactive pollution. Survey data analysis, original and unpublished results of conceptual, constructive, empirical, experimental, and theoretical work were welcome, as well as other concepts related to the radiation field.